Mechanisms and rules for preparing the municipal budget - a case study of the municipality of M’sila for the year 2023 - salmi, Abdelwahab (Journal of Research in Finance and Accounting, 2023)
The municipality is considered the basic cell for development at the local level. The legislator has granted it financial and administrative independence. From this standpoint, the municipality’s revenues and expenses are many and varied. They are classified in the budget according to forms and methods defined by the municipal law and various other laws. The process of preparing the municipal budget is subject to several stages and at each stage. It is subject to several mechanisms, some of which are defined by the financial legislator and the municipal law, and some that are subject to decrees, instructions and decisions such as compulsory expenses that cannot be reduced, and some that are subject to the authority of the Municipal People’s Assembly based on the financing capabilities of the municipality, whether it is related to the management department or the equipment department, and the legislator granted the municipality a plan Accounting through which the municipality's budget is classified into classification according to the nature of expenses and revenues, and functional classification through the division of the municipality into several functions. This study came to answer the following question: What are the mechanisms and rules that must be taken into account when preparing and preparing the municipality's budget?